Social perception of childhood overweight and obesity to generate prevention strategies in Nuevo Leon, Mexico - Garcia, Janet; Picazzo-Palencia, Esteban; Cortes-Hernández, Dora Elia; Silva-Aguilar, Kabáh (Horizonte Sanitario, 2015)
Objective . To determine the social perception on childhoodoverweight and obesity for the purpose of generating communication strategies that would prevent it through changes in behavior.Materials and methods : A descriptive study using a qualitativeresearch method that involved focus groups with children, teachersand parents. The type of analysis was argumentative. The study was conducted from January to May 2013 in the metropolitan area of Monterrey, Nuevo León, Mexico.Results : There is a most diffrent social perception among focusgroups on the quality of life and happiness of children, with parentsand teachers referring to food in relation to children happiness when it is provided as a reward or to compensate for bad experiences or lack of emotional attachment, while children refer to family harmony as the main cause for making them happy.Conclusions : The social perception reveals the importance of socialor symbolic interaction processes. Therefore, the objective of thecommunication strategy must address the associated factors inpreventing obesity through symbolic elements of these groups, taking into account the senses and meanings related to basic stimuli that trigger behaviors related to obesity